Strategi Komunikasi Pemasaran Pelayanan Kesehatan Rumah Sakit Pemerintah Untuk Masyarakat Umum - Tri Agus Yuarsa; Nafiah Ariyani; Sari Narulita (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
A good communication strategy is a strategy that can establish or position a person appropriately in communication with his or her communication partner, so as to achieve the stated communication goals. The research objective was to determine the effect of advertising, sales promotion, publicity on direct marketing in government hospital health services for the general public. Data analysis using path analysis method. The sample was selected using probability sampling technique. The research sample was 100 general hospital visitors because the number was considered to be representative of the existing population. Classical assumption testing is carried out using the normality test, linearity test, heteroscedasticity test, and multicollinearity test. Data were analyzed by multiple linear regression analysis, path analysis, and path diagrams. Processing of data analysis using SPSS software version 26.00. The research results show that there are direct and indirect positive and significant influences between advertising, promotion, publicity on direct marketing. This means that the more advertising, sales promotion, and publicity, the more direct marketing. The conclusion of the study shows that direct marketing can be increased through marketing communication strategies consisting of advertising, sales promotion and publicity. Advertising isn't the only influence on direct marketing.